Daoist identity : history, lineage, and ritual - Kohn, Livia, 1956-; Roth, Harold David (University of Hawai'i Press, 2002)
Daoist Identity is an exploration of the various means by which Daoists over the centuries have created an identity for themselves. Using modern sociological studies of identity formation as its foundation, it brings together a representative sample of in-depth analyses by eminent American and Japanese scholars in the field. The discussion begins with critical examinations of the ways identity was found among the early movements of the Way of Great Peace and the Celestial Masters. The role of sacred texts and literary culture in Daoist identity formation is discussed. The volume then focuses on lineage formation and the increasing role of popular religious practices, such as spirit-writing, in modern Daoism since the Song dynasty. Finally it discusses the Daoist adaptation and reinterpretation of Buddhist rites, such as the feeding of souls in hell and the use of ritual gestures, and the changes made in contemporary Daoism in relation to traditional rites and popular practices.